Exploring Zentangle as a virtual mindfulness-based art intervention for people with serious mental illness - Stojcevski, Marko; Cheung, Amy; Agwu, Victor; Fan, Xiaoduo (Frontiers in Psychiatry, 2023)
Introduction Zentangle is an emerging art intervention that incorporates mindfulness into creative drawing. This pilot study explored Zentangle as a novel adjunct treatment for people with serious mental illness (SMI). Methods Six participants with SMI completed an 8-week Zentangle program. Psychiatric outcomes were evaluated using the Brief Psychiatric Rating Scale (BPRS), Mindful Attention Awareness Scale (MAAS), Perceived Stress Scale (PSS), and Quality of Life Enjoyment and Satisfaction Scale (Q-LES-Q-SF). A focus group was conducted to better understand the experiences of the participants. Results A significant reduction in psychiatric symptoms was observed as measured by the total score on the BPRS between baseline and 5-week post-intervention (40.7 ± 9.1 vs. 33.7 ± 8.9, mean ± SD, p = 0.02). Participants also showed a significant increase in mindful attention using the average score on the MAAS between 1- and 5-week post-intervention (3.5 ± 0.4 vs. 4.2 ± 0.7, mean ± SD, p = 0.04). Four themes were generated from the focus group: (1) approaching mindfulness through Zentangle; (2) power of uncomplicated art creation; (3) understanding the value of self-appreciation; and (4) fostering a positive environment. Discussion Our preliminary data suggest that the use of Zentangle for participants with SMI may have a positive impact on overall psychiatric symptoms and mindfulness. Moreover, the Zentangle Method encourages positive emotions like gratitude and self-accomplishment to counteract negative feelings of self-criticism and failure in participants.